Acousto-Optical Spectral Technologies - Machikhin, Alexander S.; Pozhar, Vitold (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Acousto-optic technologies have increasingly attracted the attention of scientists and engineers. Acousto-optic interactions have become the flexible basis of compact and robust devices for the analysis of the intensity, spectrum, polarization, and other properties of light. In this book, modern trends of acousto-optical spectral technologies, including the fundamentals and optimization of existing techniques, are highlighted and discussed. This reprint provides a forum for reports on technical developments that allow the spectral analysis of various objects to take place. The goal of this reprint is to provide readers with an overview of the hot topics and the state of the art regarding the applications of acousto-optic techniques, including new materials and structures, theoretical and experimental studies of light diffraction by ultrasonic waves, spectroscopy, and spectral imaging.